Is early time to positivity of blood culture associated with clinical prognosis in patients with Klebsiella pneumoniae bloodstream infection?. (21st February 2023) - Hou, Weiwei; Han, Tiantian; Qu, Guangbo; Sun, Yehuan; Yang, Dianyu; Lin, Yan
Abstract: The association between time to positivity (TTP) of blood culture and the clinical prognosis of patients with Klebsiella pneumoniae bloodstream infection (BSI) remains unclear. A retrospective study of 148 inpatients with BSI caused by K. pneumoniae was performed at Shanghai Tongji Hospital, China, from October 2016–2020. The total in-hospital fatality rate was 32%. The median TTP was 11.0 (7.7–16.1) h and the optimal cutoff for prediction of in-hospital mortality was 9.4 h according to the ROC curve. Early TTP (<9.4 h) was a risk factor for in-hospital mortality by univariate analysis (OR = 2.5, 95% CI 1.2–5.0, P = 0.01), but not by multivariate analysis (OR = 2.7, 95% CI 1.0–7.4, P = 0.06). Old age, serum creatinine, white blood cells, and C-reactive protein values were risk factors for in-hospital mortality by multivariate analysis. Early TTP was not a risk factor for septic shock (OR = 1.8, 95% CI 0.6–5.1, P = 0.27) or ICU admission (OR = 1.0, 95% CI 1.0–1.0, P = 0.32). In conclusion, the in-hospital fatality rate of patients with K. pneumoniae BSI was relatively high and associated with an early TTP of blood cultures. However, no increased risk of mortality, septic shock or ICU admission was evident in early TTP patients.